2018
DOI: 10.3390/polym10080860
|View full text |Cite
|
Sign up to set email alerts
|

Rotation Dynamics of Star Block Copolymers under Shear Flow

Abstract: Star block-copolymers (SBCs) are macromolecules formed by a number of diblock copolymers anchored to a common central core, being the internal monomers solvophilic and the end monomers solvophobic. Recent studies have demonstrated that SBCs constitute self-assembling building blocks with specific softness, functionalization, shape and flexibility. Depending on different physical and chemical parameters, the SBCs can behave as flexible patchy particles. In this paper, we study the rotational dynamics of isolate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…with x = r/R gyr and f b (x, x b ) the bridge function defined in Eq. (23). We evaluate the set of parameters {A i , x i , x b } (i = 1, 2) by fitting only the region R min < r < R colloid , where R colloid is defined from the condition ρ (star) mon (r > R max ) σ 3 < 10 −3 , while R min is chosen to discard the profile oscillations close to the star center that are indicative of the core region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…with x = r/R gyr and f b (x, x b ) the bridge function defined in Eq. (23). We evaluate the set of parameters {A i , x i , x b } (i = 1, 2) by fitting only the region R min < r < R colloid , where R colloid is defined from the condition ρ (star) mon (r > R max ) σ 3 < 10 −3 , while R min is chosen to discard the profile oscillations close to the star center that are indicative of the core region.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this requires the inclusion of the necessary number of (MPCD) solvent particles, making the simulation of large systems quite demanding. Therefore, despite a number of works on the topic that include the study of semidilute solutions, 8,[18][19][20][21][22][23][24] the study of polymer suspensions within this framework has been limited up to now by the very high computational demand of treating the polymers in a detailed, monomer-resolved fashion while in parallel keeping track of the MPCD-solven degrees of freedom. In this respect, a suitable combination of the MPCD efficiency with a simplified model for the polymeric objects could provide a boost to the understanding of the dynamics and of the rheology of semidilute and dense suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of ω z as an angular velocity to quantify either the tumbling or the tank-treading frequency suffers from the fact that rotational vibrations are included in the calculation of ω z , which do not add to the molecule overall rotation. Recent studies , have suggested to use the corotating Eckart frame to decouple rotations from vibrations and thus better understand the dynamics of soft objects. An in-depth analysis of the rotational dynamics of the various SCNP topologies in terms of the Eckart formalism is beyond the scope of this work and will be studied in a future work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, polymers under shear flow have been shown to exhibit a rich variety of dynamic behaviors depending on the type of bonding potentials, 1,2 excluded volume interactions, 3 hydrodynamics 1,4,5 and, specially, on the molecular architecture. [6][7][8][9] The two most commonly observed reorientational behaviors at high Weissenberg numbers (i.e., when the characteristic time of the flow is shorter than longest molecular relaxation time) are: (a) tumbling motion, which is characterized by the polymer alternatingly adapting stretched and collapsed conformations over the course of which it flips 'head' over 'tail' and (b) tank-treading motion, during which the overall shape of the polymer stays approximately constant and aligned with the flow, while the individual monomers perform a rotation around the center-of-mass. Flexible linear chains are the archetypical example of polymers performing tumbling motion, as extensively discussed theoretically, 10,11 computationally [12][13][14][15][16] and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby one can obtain the so-called Eckart angular velocity Ω, which is significantly different from the "total" angular velocity ω for polymers under high shear stress. [25,26] The Eckart frame formalism has been used to calculate the rotational DoS for dimethyl sulfoxide. [27] Yang uses it to isolate the vibrational spectrum from Car-Parinello MD trajectories.…”
Section: Introductionmentioning
confidence: 99%